Sanjiao Heyi and Tibet: Resuscitating Buddhist and Daoist Perspectives - Rossow, Ty (Stance: an international undergraduate philosophy journal, 2023)
This paper considers Chinese Communist Party policies in Tibet from Confucian, Daoist, and Buddhist perspectives. I first explain how these three traditions are unified in the sanjiao heyi, but I contend that this practice has been neglected in favor of state repression. I then elucidate Confucianism, Daoism, and Buddhism with respect to their general principles and application in Tibet. I conclude that a fuller embrace of the sanjiao heyi where Confucian tenets are balanced by insights from Daoism and Buddhism would cultivate an anti-oppressive response to governmental control.